Efficiency of Pleurotus florida Laccase on Decolorization and Detoxification of the Reactive Dye Remazol Brilliant Blue R (RBBR) under Optimized Conditions. Issue 7 (12th March 2013) - Sathishkumar, Palanivel; Balan, Kannan; Palvannan, Thayumanavan; Kamala‐Kannan, Seralathan; Oh, Byung‐Taek; Rodríguez‐Couto, Susana
Abstract: Laccase from the white‐rot fungus Pleurotus florida, produced under solid‐state fermentation conditions, was used for the decolorization of reactive dye Remazol Brilliant Blue R (RBBR). RBBR was decolorized up to 46% by P. florida laccase alone in 10 min. In the presence of N ‐hydroxybenzotriazole (HBT), the rate of decolorization was enhanced 1.56‐fold. Central composite design of response surface methodology with four variables namely, dye, enzyme, redox mediator concentrations, and time at five levels was applied to optimize the RBBR decolorization. The predicted optimum level of variables for maximum RBBR decolorization (87%) was found to be 52.90 mg L −1 (RBBR), 1.87 U mL −1 (laccase), 0.85 mM (HBT), and 7.17 min (time), respectively. The validation results showed that the experimental value of RBBR decolorization (82%) was close to the predicted one. The disappearance of C–N and C–X groups, and a small shift in N–H groups in Fourier‐transform infra red (FTIR) spectroscopy confirms the degradation of RBBR chromophore by laccase enzyme. The phytotoxicity of RBBR was considerably reduced after the treatment with laccase. RBBR decolorization kinetics; K m and V max were calculated to be 145.82 mg L −1 and 24.86 mg L −1  min, respectively. Abstract : The results clearly show that N ‐hydroxybenzotriazole is an effective redox mediator for the decolorization of the dye Remazol Brilliant Blue R (RBBR). In addition, the phytotoxicity of RBBR was considerably reduced after laccase treatment. The efficiency of P. florida laccase under optimized conditions is promising in the bioremediation of dye effluents.